Research on main controlling factors of tight sandstone gas accumulation in coal-bearing strata in the southern North China Basin: Comparison with the Ordos Basin - Chen, Jingyi; Zhang, Hongwei; Chang, Hailiang; Wang, Qingwei (Frontiers in Earth Science, 2023)
Tight sandstone gas (TSG) reservoirs develop extensively in the upper Paleozoic coal bearing strata in both the southern North China Basin and the Ordos Basin. The former has not achieved important advances in TSG exploration, while the latter has built the largest TSG production facility in China. By comparing the TSG accumulation conditions in the Tongxu area of the southern North China Basin and the Fuxian area of the Ordos Basin, the main controlling factors of TSG accumulation in the southern North China Basin were analyzed in this article. The results indicate that the organic matter type of the upper Paleozoic source rocks is mainly type III kerogen, vitrinite reflectance values (Ro) are greater than 3.1%, source rocks is over mature, and the reservoir strata is characterized by low porosity and extra low permeability; therefore reservoir forming conditions are similar to those of the Ordos Basin. During the Late Jurassic-Early Cretaceous period, after a large-scale generation of hydrocarbons from source rocks in the two basins, the tectonic movements in the Yanshan period controlled the differential accumulation of TSG. The Ordos Basin has been uplifted as a whole by tectonic processes since the Triassic, which allowed a continuous deposition of Triassic strata, thus providing good sealing conditions for the upper Paleozoic TSG reservoirs. The southern North China Basin has experienced multi-stage compressive and extensive tectonic actions, so the original unified Paleozoic basin was divided into several residual blocks. However, the residual thickness of Triassic strata in slopes and sags is higher. The source rocks, reservoir strata, caprocks and overlying strata continuously deposited in time, and the time allocation of reservoir forming elements is favorable. Therefore, this is conducive to the preservation of TSG reservoirs in the upper Paleozoic. Such reservoirs are defined by high gas saturation and enriched sandstone gas.